Fonologi Bahasa Melayu Bangka di Desa Beluluk Bangka Tengah - Sausan Afra (Universitas Andalas, 2023)
This article was written (1) to describe the vocal, consonant, semivocal, and diphthong phonemes, (2) the distribution of vocals, consonants, semivocals and diphthongs, (3) Syllable patterns of Bangka Language in Beluluk Village Bangka Tengah. This research is a qualitative research with used descriptive methods. Data collected by interview techniques and used a questionnaire. This research of Bangka Language in Beluluk village Bangka Tengah has find 5 vocal phonemes with complete distribution, 16 consonant phonemes with incomplete distribution, 2 incomplete semivocal distributions, 2 diphthong incomplete distribution and 5 syllables patterns.